(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Ectopic Pregnancy also termed as extrauterine pregnancy in which the fertilised egg implantation occurs outside the uterus. Cervical ectopic pregnancy is one of the rarest form with an incidence of less than 0.1%.Cervical ectopic pregnancy is life threatening due to the high risk of bleeding if it is not treated correctly. It can be diagnosed through symptoms, ultra sound imaging and serum Hcg levels. Symptoms include bleeding and pelvic pain. Methotrexate is the drug of choice, but still there is no consensus on the most appropriate treatment for this abnormal pregnancy. In this case we discussed about a 30years old pregnant woman presented with chief complaints of bleeding, white discharge, burning micturition and a known case of diabetes and hypertension.